Civility, barbarism, and the evolution of international humanitarian law who do the laws of war protect? - Killingsworth, Matt; McCormack, Timothy L. H. (Cambridge University Press, 2023)
The history of conflict is replete with examples of exclusions from protections designed to moderate warfare. This edited volume explores how protections in modern warfare might be informed by notions of 'civility' and 'barbarism', and asks if only those deemed to be civilised are afforded protections prescribed by the laws of war"--